Analysis of a firn core for assessing POP seasonal accumulation on an alpine glacier - Villa, S; Negrelli, C; Maggi, V; Finizio, A; Vighi, M (Ecotoxicology and Environmental Safety, 2006)
Organochlorine pesticides (DDTs, HCHs, HCB) and selected PCBs were analyzed in samples from a firn core drilled on the Lys Glacier (4240m above sea level, Monte Rosa Group, Italian Alps) in Summer 2000. The samples covered a relatively short time interval (from 1997 to 2000) and a seasonal detail breakdown was possible. A probable seasonal trend was observed only for g-HCH, a pesticide currently used in some European countries. For all other chemicals, a seasonal trend was not evident, and this supports the hypothesis of the prevailing role of long-range transport in comparison with local emissions for POP pollution in high mountains. The role of temperature on air¿snow exchange has also been highlighted.